A large long standing keratinous cyst on the cheek: a case report - Save, Sneha; Mendonca, Elton; Kumar, Ravish (International Surgery Journal, 2024)
Epidermal inclusion cysts or keratinous cysts can be congenital or acquired. These slow-growing, chronic cysts can sometimes be neglected, unless they affect cosmesis or present the fear of turning malignant. We present a case of a keratinous cyst on a patient’s cheek, overlooked for many years, which slowly and steadily kept on growing and finally presenting as a disfiguring ovoid swelling over the patient’s cheek. Epithelial inclusion cysts have a tendency of slow but steady growth, with a rare of real risk of malignant change. Secondary infection, abscess formation, pressure effect and cosmetic effect are a few complications seen in such cases. Improper excision of these cysts leads to recurrence due to left over residual cyst tissue. This unearths the importance of timely investigation and treatment of swellings that we might at first assume to be insignificant.